Livestock productivity indices of transhumant agropastoralists in a grazing reserve in Northern Nigeria (2001)
The offtake and some other production parameters of transhumant agropastoralist settlers in the Bobi Grazing Reserve, Niger State, Nigeria was determined from a stratified sample of twenty percent (20%) of settlers in each of the five (5) settlement blocks in the reserve. Sample size was forty settler households who had a total of 1659 cattle, 301 sheep and 559 goats. Data collected were subjected to simple statistical analysis (Percentage, Standard Deviation, Mean). Age at first calving was between 43 and 48 months, calving interval was 16-20 months, calving percentage was 56.6% and calf mortality was 18.89% Settled pastoralists in the reserve had productivity indices that were better than national average indices, despite inadequate extension promotion and delivery facilities in the reserve.